Antagonistic effects of intraspecific cooperation and interspecific competition on thermal performance - Hsiang-Yu Tsai; Dustin R Rubenstein; Bo-Fei Chen; Mark Liu; Shih-Fan Chan; De-Pei Chen; Syuan-Jyun Sun; Tzu-Neng Yuan; Sheng-Feng Shen (eLife, 2020)
Understanding how climate-mediated biotic interactions shape thermal niche width is critical in an era of global change. Yet, most previous work on thermal niches has ignored detailed mechanistic information about the relationship between temperature and organismal performance, which can be described by a thermal performance curve. Here, we develop a model that predicts the width of thermal performance curves will be narrower in the presence of interspecific competitors, causing a species’ optimal breeding temperature to diverge from that of its competitor. We test this prediction in the Asian burying beetle Nicrophorus nepalensis, confirming that the divergence in actual and optimal breeding temperatures is the result of competition with their primary competitor, blowflies. However, we further show that intraspecific cooperation enables beetles to outcompete blowflies by recovering their optimal breeding temperature. Ultimately, linking abiotic factors and biotic interactions on niche width will be critical for understanding species-specific responses to climate change.